CASH on Modified Elgamal: A Preventive Technique for False Channel Condition Reporting Attackin Ad-hoc Network. (2016) - Sridhar, A.; Josna, V.R.
Abstract: Ad-hoc networks are wireless networks, where the nodes transmit data through other nodes. Many Wireless networks exploit channel condition for routing. Such protocols are known as channel aware protocols. In channel aware protocols, each node reports its channel condition to other nodes and other nodes give its channel condition. However these protocols are vulnerable to false channel condition reporting attack. In this paper, an efficient Coordinate ASH (CASH) algorithm on Modified elgamal signature is proposed to avoid false channel condition reporting attack. Message authentication is ensured by adding signature and this signature is added to routing messages. Analysis demonstrates that proposed scheme is better than current schemes with respect to Computational time.